Pemberdayaan Ibu PKK melalui Pengolahan Residu Cocofiber menjadi Coco Pot Ramah Lingkungan di Desa Kedayunan - Nanda Rusti; Danang Sudarso Widya Prakoso Joyo Widakdo; Eka Nurmala Sari (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Cocofiber residue from cocopeat processing in Kedayunan Village has not been productively processed because PKK members have limited access to simple processing technology. This program aimed to strengthen participants' capacity to produce eco-friendly coco pots. Participatory training and mentoring were conducted on 6 May 2026 with 25 participants, covering needs identification, environmental education, wire frame fabrication, cocofiber arrangement, finishing, and evaluation. Data were collected through observation, documentation, a 10-item pretest–posttest, and a five-criterion skills rubric. The mean knowledge score increased from 88% to 96%, an increase of 8 percentage points. More importantly, participants converted prior knowledge into practical experience and collectively produced 28 cylindrical prototypes with a diameter of approximately 17 cm. The main constraints were inconsistent frame dimensions, uneven fiber density, and inconsistent surface finishing. Verified short-term outcomes included improved understanding, basic product-making skills, and working prototypes; economic and environmental impacts have not yet been measured. Follow-up actions should prioritize product standardization, durability testing, cost calculation, branding, and local marketing through PKK networks and village institutions.